A pharmacoinformatic approach for studying Atractylodes Lancea DC’s anticancer potential and control ROS-mediated apoptosis against prostate cancer cells - Ahn, Chi-Hoon; Myong, Ji Soo; Ahmed, Kazi Rejvee; Rahman, Md Ataur; Fahim, Md. Maharub Hossain; Choi, Min; Rahman, Muntajin; Choi, Jinwon; Kim, Kiryang; Moon, Seungjoon; Dalli, Mohammed; Syahputra, Rony Abdi; et al. (Frontiers in Oncology, 2025)
IntroductionProstate cancer (PCa) is a malignancy characterized by abnormal cell proliferation in the prostate gland, a critical component of the male reproductive system. Atractylodes lancea DC. (ALD), a medicinal herb commonly used in traditional Asian medicine, is highly regarded for its antioxidant, antidiabetic, and anticancer properties. Virtual docking stud-ies have identified Atractylenolide II and III as active components of ALD, demonstrating strong binding potential to inhibit androgen receptor (AR) activity, with docking scores of -8.9 and -9.3, respectively. These findings suggest that ALD may exert a synergistic effect comparable to or greater than that of enzalutamide (ENZ) in inhibiting AR. How-ever, its specific anticancer and anti-metastatic mechanisms in prostate cancer remain unclear.MethodsThe cytotoxic effects of ALD were evaluated on PC3 and DU145 prostate cancer cells, as well as on the normal prostate cell line BPH-1. Cell viability was assessed using the EZ-Cytotoxic kit, while colony formation assays and TUNEL staining were used to meas-ure proliferation and apoptosis, respectively. Apoptosis was further analyzed through an-nexin V-FITC/PI staining and quantified by flow cytometry (FACS). Western blotting was performed to elucidate the underlying molecular mechanisms. Additionally, mito-chondrial membrane potential (ΔΨm) and intracellular calcium levels were measured to evaluate mitochondrial function, while reactive oxygen species (ROS) generation was assessed with and without pretreatment with N-acetylcysteine (NAC) .ResultsALD selectively reduced the viability of PC3 and DU145 prostate cancer cells while spar-ing BPH-1 normal prostate cells, demonstrating cancer-selective cytotoxicity. ALD dis-rupted mitochondrial function by reducing ΔΨm and increasing intracellular calcium lev-els. A concentration-dependent increase in ROS generation was observed in PC3 and DU145 cells, which was completely inhibited by NAC pretreatment, confirming a ROS-mediated mechanism. Colony formation assays revealed a significant reduction in prolif-eration, while TUNEL and annexin V-FITC/PI staining indicated enhanced apoptosis. Western blot analysis showed that ALD modulates critical survival pathways, leading to apoptotic cell death.DiscussionThese findings demonstrate that ALD exerts potent anticancer effects against metastatic prostate cancer cells through ROS-mediated apoptosis and mitochondrial dysfunction, while exhibiting minimal cytotoxicity toward normal prostate cells. The presence of ac-tive compounds such as Atractylenolide II and III suggests a synergistic interaction that enhances AR inhibition and promotes apoptosis. ALD’s ability to engage multiple path-ways highlights its therapeutic potential as a selective and multifaceted treatment for ag-gressive prostate cancer.